Electronic Commerce 2018 - Turban, Efraim; Outland, Jon; King, David; Lee, Jae Kyu; Liang, Ting-Peng; Turban, Deborrah C. (Springer, 2018)
Electronic commerce, the topic of this book, has grown rapidly, with companies like Facebook, Google, Pinterest, LinkedIn, Uber, Alibaba Group, and Amazon.com setting new levels of performance every year. Electronic commerce (EC) is a business model in which transactions take place over electronic networks, mostly the Internet. It includes the process of electronically buying and selling goods, services, and information. Certain EC applications, such as online buying and selling stocks and airline tickets, are reaching maturity, some even exceeding non-Internet trade volume. However, EC is not just about buying and selling; it also is about electronically innovating, communicating, collaborating, and discovering information. It is about e-learning, e-customer service, e-government, social networking, problem-solving, and much more. EC is having an impact on a significant portion of the world, affecting businesses, professions, trade, and, of course, people. It is undoubtedly improving our quality of life. A most important development in EC since 2014 is the phenomenal growth of social network services, especially Facebook, Google+, and Twitter. Also impressive is the trend toward conducting EC via mobile devices. Another major development is the global expansion of EC, especially in China, where you can find the world’s largest EC company. In addition, attention is given to artificial intelligence and its applications and to smart commerce as well as to the use of analytics and big data to enhance EC. Finally, some emerging EC business models are transforming industries (e.g., travel, banking, fashion, and transportation). In the ninth edition (2017–2018), we bring forth the latest trends in e-commerce, including smart commerce, social commerce, social collaboration, shared economy, innovations, and mobility.
A Managerial and Social Networks Perspective